Sacralization of Politics ın the Context of Modern Georgia - Sumbadze, Nana; Maglakelidze, Erekle; Menagarishvili, Anna; Abzianidze, Shalva (European Scientific Journal, ESJ, 2017)
Sacralization of politics characterizes tyrannies and democracies alike, functioning as strengthening power bases and maintaining continuity of collective identity. The goal of the study was to register these two directional processes in the modern political context of Georgia. The political landscape of Georgia after gaining independence is characterized by oscillation of voters between charismatic and rational leaders. Inauguration speeches of the presidents were subjected to thematic analysis to reveal religious allusions. All of them although to a different degree refereed to five main themes: Holy path and trial, hierarchies and Gods, rituals, national religious consciousness and anti secularism. Analysis proved the resemblance between the first and the third presidents, both being charismatic, emotional leaders, most often referring to holly path and trial, and religious national consciousness in contrast to the second president, who was steered more by rationality than emotion, referring to hierarchies and Gods, and rituals. Estimations of young voters of the leaders pointed to the preference to the first president – Gamsakhurdia. The idealization of the leaders occurred more in regard to charismatic leaders by those who proved to be less tolerant of ambiguity and hence, more striving to sustain black and white worldview. This result with some precautious can be taken as an indicator of the need to sacralize the leader and thus to maintain continuity and stability of collective identity.